Bringing Care Governance to Ontario's Retirement Homes Sector - Blair Roblin; Raisa Deber; Kerry Kuluski; Michelle Silver (McMaster University Library Press, 2019)
In 2010, the Ontario government introduced Bill 21, the Retirement Homes Act, 2010 (the Act), which required the licensing of retirement homes (RHs), residents' rights, care and safety standards, inspections, compliance and a newly formed Retirement Homes Regulatory Authority (Authority). The Act and its regulations drew heavily from the content of legislation pertaining to long-term care homes (LTC homes), recognizing that many RHs provided high acuity care. However, the Authority was constituted with a multi-sectoral board, which was arm's length from government. The stated goal of the Act was to ensure the dignity, respect, safety and privacy of residents, though the government also recognized the importance of preserving autonomy and choice for the predominantly private, for-profit operators and their residents. A consultation process spurred considerable debate over the content of the proposed legislation as well as the authority that would oversee it. The unwillingness of the government to fund care services in RHs (unlike LTC homes) influenced its policy decision to pass the Act in a form that gave greater autonomy to the industry to oversee its regulation through a multi-sectoral Authority, rather than one directed by government. A formal five-year review showed the reform to be well received by the public and key stakeholders, and an Effectiveness Survey for Stakeholders conducted by a third party indicated positive results, pointing to the success of both regulatory content and oversight.